Time evolution of electrical impedance spectra of Staphylococcus aureus and Escherichia coli bacteria - Miranda Mercado, David Alejandro; Godoy Alarcón, Erika Viviana [UNESP]; V-Niño, Ely Dannier (Elsevier, 2024)
This research work reports the time evolution of the electrical properties of gram-positive and gram-negative bacteria in aqueous suspensions with methyl violet and Lugol; measurements of galvanostatic electrical impedance spectra were made in a frequency range of 10Hz to 100kHz. The magnitude of the impedance as a function of frequency for methicillin-resistant strains, Staphylococcus aureus (gram-positive), and Escherichia coli O157: H7 (gram-negative) in the presence of methyl violet and Lugol, showed that both strains exhibited a progressive decrease in the magnitude of the electrical impedance with an increasing bacterial population; however, the variation in the magnitude rate of the impedance over time is completely different between the gram-positive and gram-negative strains. The results suggest that the time evolution of the electrical impedance spectra can be used to differentiate Staphylococcus aureus from Escherichia coli bacteria.
Keywords: Gram-negative; Gram-positive; Impedance measurement; Lugol; Methyl violet